Clinically silent LINE 1 insertion in the PNPLA3 gene may impede genotyping of the p.I148M variant - Leníček, Martin; Šmíd, Václav; Pajer, Petr; Nazarova, Anna; Dvořák, Karel; Subhanová, Iva; Brůha, Radan; Vítek, Libor (Scientific reports, 2021)
The patatin-like phospholipase domain containing 3 ( PNPLA3 ) gene (viz. its I148M variant) is one of the key players in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). We have identified a novel insertion/deletion variant of 1114 bp, localized in the second intron of the PNPLA3 gene, which corresponds to the 3′ terminal sequence of the long-interspersed element (LINE-1). DNA analysis of 122 NAFLD patients and 167 control subjects as well as RNA analysis of 19 liver biopsies revealed that the novel variant is very common (frequency = 0.41), fully linked to the clinically important I148M variant, and clinically silent. Although the LINE-1 insertion does not seem to have any biological effect, it can impede genotyping of the I148M variant. If insertion prevents the attachment of the diagnostic primer, then the non-insertion allele will be selectively amplified; and thus the frequency of the 148M "risk" allele will be significantly overestimated due to the complete linkage of the LINE-1 insertion and the 148I allele of the PNPLA3 gene. Therefore, our findings underline the importance of careful design and consistent documentation of the methodology, including primer sequences. Critical revisions of the results of some studies that have already been reported may therefore be needed.